Nutrisi Brownies Tepung Buah Mangrove (Avicennia officinalis) dan Tepung Kacang Merah Sebagai Pangan Fungsional - Sumartini; Kurnia Sada Harahap; Apri Mujianti (Jurnal Airaha, 2020)
The purpose of this study is to know the potential of functional food contained in mangrove fruit flour is reviewed from its nutritional value. Brownies can be produced from various of flour, there is api api fruit flour (A) red kidney bean flour (B) and wheat flour as control (C). The chocolate brownies that have been produced then tested the panelist preference level through a hedonic test. Furthermore, brownies tested nutrition value, crude fiber content, and proximat value such as moisture content, fat content, protein content, ash content, and carbohydrate content. The method used is experimental design with a completely randomized design. The results showed that chocolate brownies made from mangrove fruit flour were preferred by panelists, besides having high calories and fiber content they also contained nutrients needed by the body through proximate testing, with water content values ranging from 18.32%, fat content 21, 7%, 4.68% protein content, 1.44% ash content, 54.64% carbohydrate, 16.49% fiber content and 401.64 kcal calorie value. The conclusion of the research that mangrove flour and red bean flour brownies were proven to have nutritional content and a higher level of consumer acceptance than brownies made from wheat flour